Experimental Study of Supercavitation Bubble Development over Bodies in a Free-Surface Flow - Lotan Arad Ludar; Alon Gany (Journal of Marine Science and Engineering, 2022)
This research conducts experimental studies on supercavitation bubble development and characteristics within free-surface water and the role of cavitator, comparing the results to those of similar experiments carried on in a duct flow. Tests have been conducted on cylindrical bodies (47 mm diameter) moving underwater at different velocities in a 10-m-diameter circular pool of about 50 cm water level. A comparison has been made for supercavitation bubbles resulting from six different cavitator geometries (flat, sphere, cone, ogive, inverted sphere, and truncated cone). The comparison referred to the conditions of the bubble formation, as well as to the shape and development. It was found that the different cavitators produced different bubble geometries as opposed to the results of experiments conducted in a duct flow by the authors. Nevertheless, the order of onset of cavitation bubble creation (with relation to the cavitation number and flow velocity) was similar. One of the conclusions of this study was that the pressure difference used for defining the cavitation number has a significant impact on the correlation between the bubble characteristics and cavitation number. This fact should be considered when comparing data from different sources.